Music in Virtual Reality: New Opportunities for Composers and Performers - Yuldashev, Akmaljon (Indonesian Journal Publisher, 2024)
Virtual reality provides the opportunity to experience unique visual and audio experiences that directly impact our senses. A virtual reality headset allows you to create the feeling of being in another world or situation, opening up new horizons for exploration and creativity. When we talk about music in virtual reality, it means that the sound elements become an integral part of the simulated environment. Music can complement visuals and help create a more complete and engaging virtual experience for the user. The method employed involves a comprehensive examination, spanning the conceptual understanding of virtual reality, its transformative impact on the music industry, and the pivotal role of composers in this dynamic landscape. The ultimate outcome is a tapestry of music that not only complements visuals but actively responds to user interactions, creating a novel and deeply engaging auditory journey within the realms of virtual reality.